O professor de matemática e a análise exploratória de dados no ensino médio - Cardoso, Ricardo (2007)
Statistics has stand out lately due to its utility in almost every area of human knowledge. Existing research and essay on the subject suggest the need for deepening knowledge on the difficulties with teaching process of this discipline. Our main issue is to investigate whether Brazilian public school teachers develop the Descriptive Statistics in high school and whether they are able to use, efficiently, the basic statistics concepts Data Organization, Measures of Central Tendency, Separatrixes and Dispersion to solve daily practical problems. The aim of this research is to verify the level of knowledge mobilization by high-school teachers. According to LINS (2004, p.54) we know that the general impression not registered systematically by researches that the licenciate s mathematical formation, in great part similar to the future graduate, does not contribute substantially to the formation of this future professional, unless to reinforce the expositive classes routines . We will try to diagnose in which level of knowledge the high-school teacher is in school curriculum of Statistics. Based on BIFI s questionnaire (2006, p.54), we will verify whether the high-school Mathematics teacher is able to calculate, justify and relate the described measures. The answers of the activities will be analyzed through C.H.I.C. software